PERAN TATA KELOLA PERUSAHAAN DAN RISIKO PELAPORAN KEUANGAN DALAM PEMBENTUKAN KOMITE MANAJEMEN RISIKO YANG TERPISAH - Yessi Arifina (Universitas Katolik Soegijapranata Semarang, 2017)
Abstract This study examines the effect of board size, board independence, financial reporting risk, firm complexity, and firm size on the formation of risk management committees apart from audit committee. This study predicts the increasing number of board of size improve the supervisory function and encourage the formation of separate risk management committees. The higher the independence of the board of commissioners, the better the supervision will be and encourage the formation of separate risk management committees. The larger the company's business segments the risks faced by the company will also be greater and this will encourage the formation of separate risk management committees. Large companies have greater responsibility to shareholders than small companies. Therefore, companies are required to perform more effective oversight functions. This will encourage companies to form separate risk management committees. The results show that board size has a positive effect on the formation of separate risk management committees. Financial reporting risk negatively affect the formation of separate risk management committees. Mean while board independence, company complexity, and firm size have no effect on the formation of separate risk management committees.